PENGGUNAAN ASAS-ASAS FILOSOFIS DALAM PENGEMBANGAN DAN PELAKSANAAN KURIKULUM MERDEKA - Cintya Permatasari Pata’dungan; Misel Pilemon, Noflianti Rapang, Mari Mangguali, Dina (CV. ADIBA ASIHA AMIRA, 2025)
This research aims to analyze the use of philosophical principles in the development and implementation of the